In-service EFL students’ peer assessment for the enhancement of their writing skills - Zekarias , Adane Paulos (Univeritas Papua, 2022)
This study attempted to investigate the extent to which peer assessment activities contribute to enhance in-service EFL students’ writing skills. Based on the constructivist theory, a case study design was implemented and both qualitative and quantitative research approaches were used to explore how 120 in-service students at Dilla University, Ethiopia, took part and responded to peer assessment activities to improve their writing competencies. Data was gathered through four tools, namely, questionnaire, focus group interviews, observation and document analysis. The findings suggest that peer assessment activity, though students’ perceptions and past experience impact, can aid peers in developing their writing performance through interaction, sharing feedback and addressing the challenges they face in the process of writing.